PERAN PUSAT PERPUSTAKAAN DAN PENYEBARAN TEKNOLOGI PERTANIAN DALAM TUJUAN PEMBANGUNAN BERKELANJUTAN - Rufaidah, Vivit Wardah; Iskak, Penny Ismiati (Association of Indonesian Library and Information Professionals, 2019)
The Sustainable Development Goals (SDGs) are aligned with Indonesia's national development priorities set out in the National Medium Term Development Plan. Of the 169 SDGs targets, around 57 percent of SDGs are in line with national development priorities. Agriculture is closely related to achieving SDGs. Agricultural development driven by the Ministry of Agriculture of the Republic of Indonesia is included in second goal and 8th on achieving SDGs in Indonesia. The second goal is to eliminate hunger, achieve? food security, good nutrition, and improve sustainable agriculture. Whereas, the 8th goal is to promote inclusive and sustainable economic growth, productive and comprehensive employment opportunities, and decent work for all. In the second quarter of 2017, the agricultural sector contributed 13.92 percent (up 0.33 percent from the first quarter of 2017) to economic growth. In addition to absorbing labor (31.86% of the workforce), agriculture also provides food, industrial raw materials, feed and bio-energy and contributes to foreign exchange of US 8.24 billion. Innovation is very important in the success of agricultural development. Information plays an important role in the application of innovation by agricultural actors. The Indonesian Center for Agricultural Library and Agricultural Technology Dissemination plays a role in providing information related to agricultural innovation and promoting agricultural literacy in the community. The activities of agricultural literacy conducted by PUSTAKA include: 1) agricultural literacy workshop among students and extension workers, 2) increasing video collections of agricultural technology, 3) agricultural literacy in Taman Baca, 4) building Kid Corner and completing it with library material in agriculture , 5) visit Agricultural Technology and Science Parks, 6) exhibitions, and 7) technical guidance for farmers by presenting resource persons who are experts in agriculture. Through agricultural literacy, the community have been able to utilize information resources such as iTani, the Agricultural Publication Repository and the agricultural information provider website. In the end, it is expected that the community will more quickly adopt agricultural innovations.